ANALISIS FAKTOR INTERNAL DAN FAKTOR EKSTERNAL YANG BERKAITAN DENGAN HASIL BELAJAR PRAKTIK PELURUSAN DAN PENGERITINGAN RAMBUT KELAS XI DI SMKN 3 TANGERANG - Nurul Amalia; Mari Okatini Armandari; Neneng Siti Silfi Ambarwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the internal and external factors associated with the learning outcomes of Hair Straightening and Hair Perming practical courses among eleventh-grade Hair Beauty students at SMKN 3 Tangerang. This research employed a quantitative approach using a survey method. The study population consisted of 65 students, all of whom were selected as the sample using a saturated sampling technique. Data were collected through questionnaires to measure internal and external factors, while students' practical learning outcomes were obtained from their practical assessment scores. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results showed that internal factors did not have a significant relationship with the learning outcomes of Hair Straightening and Hair Perming practice, with a significance value of 0.879 (> 0.05). In contrast, external factors had a significant effect on learning outcomes, with a significance value of 0.010 (< 0.05). These findings indicate that external factors play a more dominant role than internal factors in influencing students' learning outcomes. Based on the results, it can be concluded that improvements in students' practical learning outcomes in Hair Straightening and Hair Perming are influenced more by external factors than by internal factors. Therefore, schools, teachers, parents, and students are expected to work collaboratively to create a conducive learning environment, improve the quality of instruction, and optimize practical learning facilities to enhance students' learning outcomes.